2019
DOI: 10.1038/s41436-018-0280-5
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Opportunities to implement a sustainable genomic medicine program: lessons learned from the IGNITE Network

Abstract: The original version of this Article contained an error in the spelling of the author Geoffrey S. Ginsburg, which was incorrectly given as Geoffrey Ginsburg. This has now been corrected in both the PDF and HTML versions of the Article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…As noted, in this survey, we did not inquire whether reimbursement was received by IGNITE member sites when laboratories billed third party payers. Previous studies [8] have shown the importance of reimbursement for implementation and sustainability of genomic testing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As noted, in this survey, we did not inquire whether reimbursement was received by IGNITE member sites when laboratories billed third party payers. Previous studies [8] have shown the importance of reimbursement for implementation and sustainability of genomic testing.…”
Section: Discussionmentioning
confidence: 99%
“…7 National Human Genome Research Institute, Bethesda, MD, USA. 8 Mission Health, Fullerton Genetics Center, Ashville, North Carolina, USA. 9 Nemours Children's Specialty Care, Jacksonville, Florida, USA.…”
Section: Acknowledgementsmentioning
confidence: 99%
See 1 more Smart Citation